PERANCANGAN INTERNET OF THINGS (IOT) SMART HOME - Afrizal Zein; Emi Sita Eriana (Institut Sains dan Teknologi Nasional, 2021)
The main purpose of this research is to design a smart home using IoT where the technology is to automate various activities at home such as turning off and turning on the lights, television, air conditioner, fan sound system and opening the gate. All devices are connected to the internet via a router, to allow remote monitoring and control of various household appliances. In this paper, I implemented a smart home using the newly released cisco tracer package simulation software, because different IoT devices used for home automation are included in this new version of the simulator. The previous software only had network devices, but in the newly released IoT simulator devices are included sensors, boards, IoT devices. To smartly design the house I use different devices that are used for home security, safety and well-being of the home environment. Keywords: IoT, Smart home, packer tracer, sensor.